A novel and non‐invasive approach utilising nasal washings for the detection of nasopharyngeal carcinoma - Tan, Geok Wee; Sivanesan, Vijaya Mohan; Abdul Rahman, Farah Ida; Hassan, Faridah; Hasbullah, Harissa Husainy; Ng, Ching Ching; Khoo, Alan Soo Beng; Tan, Lu Ping (John Wiley & Sons, 2019)
Nasopharyngeal carcinoma (NPC) is an epithelial cancer of the nasopharynx which is highly associated with Epstein–Barr virus (EBV). Worldwide, most of the top 20 countries with the highest incidence and mortality rates of NPC are low- and middle-income countries. Many studies had demonstrated that EBV could be detected in the tissue, serum and plasma of NPC patients. In this study, we explored the potential of assays based on non-invasive nasal washings (NW) as a diagnostic and prognostic tool for NPC. A total of 128 patients were evaluated for NW EBV DNA loads and a subset of these samples were also tested for 27 EBV and human miRNAs shortlisted from literature. EBV DNA and seven miRNAs showed area under the receiver operating characteristic curve (AUC) values of more than 0.7, suggestive of their potential utility to detect NPC. Logistic regression analyses suggested that combination of two NW assays that test for EBNA-1 and hsa-miR-21 had the best performance in detecting NPC. The trend of NW EBV DNA load matched with clinical outcome of 71.4% (10 out of 14) NPC patients being followed-up. In summary, the non-invasive NW testing panel may be particularly useful for NPC screening in remote areas where healthcare facilities and otolaryngologists are lacking, and may encourage frequent testing of individuals in the high risk groups who are reluctant to have their blood tested. However, further validation in an independent cohort is required to strengthen the utility of this testing panel as a non-invasive detection tool for NPC. © 2019 The Authors. International Journal of Cancer published by John Wiley & Sons Ltd on behalf of UICC